(untitled) (International journal of artificial intelligence, 2025)
Early motor development is a vital indicator of neurological functioning in infants. Research increasingly suggests that motor activity differences may emerge in infants later diagnosed with autism spectrum disorder well before the first signs of social or communication challenges. This article explores the current tools used to assess motor behaviors in infants under six months of age and their relevance for early identification of autism. Highlighting modern, evidence-based observational methods and standardized assessments, the article discusses how early motor markers could enhance screening accuracy and support earlier intervention.